2013
DOI: 10.1039/c2cc37268a
|View full text |Cite
|
Sign up to set email alerts
|

Label-free in situ detection of individual macromolecular assemblies by surface enhanced Raman scattering

Abstract: We demonstrate label-free detection of lipid vesicles and polystyrene beads freely diffusing in aqueous solution using surface enhanced Raman scattering (SERS). The signals observed enable real-time identification and monitoring of individual particles interacting with the SERS substrate. SERS is demonstrated as a label-free method capable of monitoring transient species in solution on the millisecond time scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 20 publications
(34 reference statements)
0
39
0
Order By: Relevance
“…However, the limit of detection of 2-D substrates in solution is still controlled by transport, which can hinder analyte interaction with the SERS-active surface. 24 Over the years, methods have been developed to increase substrate-analyte interactions. Chemical modifications have been shown to increase affinity of the analyte molecules for the SERS substrate.…”
Section: Introductionmentioning
confidence: 99%
“…However, the limit of detection of 2-D substrates in solution is still controlled by transport, which can hinder analyte interaction with the SERS-active surface. 24 Over the years, methods have been developed to increase substrate-analyte interactions. Chemical modifications have been shown to increase affinity of the analyte molecules for the SERS substrate.…”
Section: Introductionmentioning
confidence: 99%
“…We previously showed a similar effect for the transient detection of lipid vesicles, where the interaction with the surface lasted on the order of 100 ms and signal acquisitions of several seconds did not provide detectable signals. 26 In Figure 2C, we observe that a clear spectrum can be obtained from DSERS analysis.…”
Section: Resultsmentioning
confidence: 82%
“…1 a shows the setup used to perform the SERS experiments. Ag rough surface) 28,29 . 1 b displays the state-of-art gold coated plasmonic nanopores 6 which are shown to be capable of optically trapping 20 nm polystyrene beads 7 and localizing the SERS detection region in small volumes with high enhancement 8 .…”
Section: Sers and Particle Trapping In Plasmonic Nanoporesmentioning
confidence: 99%
“…The first thing that strikes our attention is that the strongest peak at 998 cm-1 in the bulk Raman spectrum of polystyrene, assigned to the aromatic ring breathing mode 31 , is absent in the SERS spectra taken on both the rough surface and inside the nanopore (see Fig. For 100-1000 nm particles 28,29 it is shown that the ring breathing mode can be observed. The only visible Raman peak in both SERS spectra is near 785 cm -1 , also appearing in the bulk Raman spectrum at 792 cm -1 , assigned to vibration of aromatic rings linked through gauche-gauche conformations of the aliphatic chain 31 .…”
Section: Figmentioning
confidence: 99%